PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Kiki Noviem Mery; Zulbahridar '; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aim to examine The Effect of Liquidity, Leverage and Profitability of the Corporate’s Value with Dividend Policy as Moderation on Mining Companies at The Indonesia Stock Exchange Year 2011-2014. The study population was 42 companies, but based on the criteria there are only 10 (ten) companies. The population used in this study were Mining Companies at The Indonesia Stock Exchange (IDX) Year 2011-2014.The data used in this research is secondary data and sample selection by using purpossive sampling technique while data analysis using multiple linear regression model. The analysis tool used is multiple regression analysis using SPSS 20. The study states that the Liquidity significantly affects the corporate’s value. Leverage has no significant effect to the corporate’s value. Profitability has a significant effect to the corporate’s value. Liquidity moderated by dividend policy has a significantly influence to the corporate’s value. Leverage moderated by dividend policy no significant effect on the corporate’s value. Profitability moderated by dividend policy has a significantly influence to the corporate’s value.Keywords: Liquidity, Leverage, Profitability, Dividend Policy, and Corporate Values